RANCANG BANGUN BOILER VERTIKAL UNTUK INDUSTRI TAHU: RANCANG BANGUN BOILER VERTIKAL UNTUK INDUSTRI TAHU - Gafur, Abdul Gafur; Imran, Imran (Politeknik Negeri Bengkalis, 2023)
This research is to design and manufacture a vertical boiler for boiling tofu. Conventional boiling of tofu takes a long time, for 10 kg of mashed soybeans it takes up to 60 minutes. Therefore a boiler is designed to speed up the boiling process. The designed boiler is a vertical type boiler with firetube boiler pipes using the ASME (American Society of Mechanical Engineers) design standard and making design drawings using the Autodesk Inventor software version 2017. The results of the study obtained the internal pressure boiler design specifications of 3 bar and operating pressure of 2 bar. With the dimensions of the boiler, namely a diameter of 500 mm, a height of 1200 mm and in it there are fire pipes with a diameter of 40 mm, a length of 100 mm and a total of 17 pieces. The material used is carbon steel SA 285 GRADE C and seamless carbon steel pipes SA 53 Grade B. Seamless carbon steel SA 53 Grade B and the fuel used is wood. Initial test results by varying the pressure from 1, 1.5, 2, and 2.5 bar with an average heating time of about 50 minutes with air temperature reaching 122 0C and steam temperature 130 0C.